"Brain Death, " "Dead, " and Parental Denial. (17th July 2014) - PARIS, JOHN J.; CUMMINGS, BRIAN M.; MOORE, M. PATRICK
<x content-type="archive" xml:space="preserve">Abstract</x> This section provides reactions to current and emerging issues in bioethics.